Limiting the access to direct-acting antivirals against HCV: an ethical dilemma. (1st November 2016) - Gentile, Ivan; Maraolo, Alberto E.; Niola, Massimo; Graziano, Vincenzo; Borgia, Guglielmo; Paternoster, Mariano
ABSTRACT: Introduction: Hepatitis C virus (HCV) infection affects about 200 million people worldwide and represents a leading cause of liver-related mortality. Eradication of HCV infection, achieved mainly through direct-acting antivirals (DAA), results in a decrease of mortality and an improvement of quality of life. These drugs have a maximal efficacy and an optimal tolerability. However, their high cost precludes a universal access even in wealthy countries. Areas covered: This article deals with the policies adopted for the use of the new anti-HCV drugs, especially in Europe and most of all in Italy, supposedly the developed country with the highest HCV prevalence. The literature search was performed using Pubmed and Web of Science. Moreover, national regulatory institutional websites were consulted. Expert commentary: The current policy of limitation to the access of the DAA presents a series of ethical issues that makes it non-applicable. A 'treat-all' strategy should resolve all ethical dilemmas, by virtue of the wide benefits of anti-HCV treatment not only for the advanced stage of infection, but also for the initial stages. A reduction in price of the drugs is the actual condition to achieve such a change.